How to examine a patient with skin cancer. (July 2017) - Craythorne, Emma; Al-Niami, Firas
Abstract: The incidence of skin cancer is increasing dramatically worldwide, and with heightened public awareness, patients present with skin cancers at an earlier stage. Although most non-melanoma skin cancers occur on exposed sites, potentially lethal malignant melanoma tends to occur under clothing. Complete skin examination allows the detection of the lesion the patient presents with and any other the physician may find. The skin examination also allows for a 'teachable moment' to educate the patient in self-examination.